Desvelando a família homoparental: um estudo sobre os relatos de casais homossexuais com filhos - Tombolato, Mário Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The homoparental family emerges is the multtitude of alternative living arrangements in today's world. It allows for same-sex couples to exercise parenthood in a way that is still marginally studied in the Brazilian context. The main objective in this study was to investigate how homosexual couples live with their children by analyzing personal accounts and reports. Five homosexual couples, two male and three female, with either biological or adopted children have participated. The data were collected via one socioeconomic questionnaire and one semi-structured interview that was audio-recorded and trascribed verbatim for content analysis. The following and subcategories have been established and discussed: (1) motivations for parenthood living with children in the family; subjective and social motivations; and differences between the partners; (2) procedures to attain parenthood: adoption, assisted human reproduction; and child of a previous heterosexual; (3) family routines and the rearing of children: how couples live after the arrival of children; family routiness concerning child rearing and upbringing; the characteristics of parental functions; acceptance and the ways in which children address their mothers and fathers; (4) the relations between the homoparental family with the families of origin: changes in family relations after the arrival of children; family support: the contribution of family members and granpparents in childcare; limited or non-existent contact with families of origin; (5) homoparental families and society; prejudice, discrimination and recognition of rights; social surveillance; networks for social suuport; and benefits and challenges for homoparental families. The findings reveal recurring factors concerning homosexuality with regard to members of the families of origin, motivations and experiences to attain parenthood shared by homosexual couples, family routines and childcare, and how homoparental...

A família homoparental emerge dentro da pluralidade dos alternativos arranjos familiares dos dias de hoje. É nela que pessoas de orientação sexual homossexual exercem a parentalidade, uma situação ainda pouco estudada na realidade brasileira. O objetivo geral dessa pesquisa foi investigar, a partir de relatos, a vivência enquanto família de casais homossexuais com filhos. Participaram cinco casais homossexuais, dois de pares homens e três de pares mulheres, que tinham filhos - biológicos e/ou adotados. A coleta de dados foi realizada por meio de um questionário socioeconômico e uma entrevista semiestruturada que foi áudio-gravada e transcrita na íntegra para análise de conteúdo. As categorias e subcategorias identificadas e analisadas foram: (1) As motivações para a parentalidade: convivência com crianças familiares; motivações e sociais; e divergências entre o casal; (2) Os procedimentos de acesso à parentalidade: adoção; reprodução humana assistida; e filha de um relacionamento heterossexual anterior; (3) A rotina familiar e a criação dos filhos; a vida dos casais após a chegada dos filhos; a rotina familiar nos cuidados dos filhos; as características das funções parentais; os cuidados na criação dos filhos; a aceitação e os modos como os filhos chamam pelos pais e mães; (4) As relações da família homoparental com sua família de origem: modificações nas relações familiares após a chegada das filhas dos casais; suporte familiar: a contribuição dos familiares e avós nos cuidados com as crianças: pouco ou sem contato com os familiares de origem; (5) As famílias homoparentais e a sociedade: preconceito, discriminação e reconhecimento de direitos; vigia social; redes de apoio social; e facilidades e dificuldades da família homoparental. Os resultados demonstraram recorrência de características quanto à homossexualidade no âmbito dos familiares de origem, às motivações e vivências...
Keywords: Homoparentalidade; Casamento entre homossexuais; Família; Maternidade; Paternidade; Gay parents